Mixed feeding schedule of low and high protein in the diet of Labeo rohita (Hamilton) fingerlings: effect on growth performance, haemato‐immunological and stress responses. (4th February 2015) - Xavier, B.; Jain, K.K.; Pal, A.K.; Sahu, N.P.; Maheswarudu, G.; Gal, D.; Kumar, S.
Abstract: Four experimental diets D1, D2, D3 and D4 having 100, 300, 350 and 400 g protein kg −1 diet, respectively, were prepared. Fingerlings of Labeo rohita (5.45 ± 0.03 g) were fed with different diets following a mixed feeding schedule with the feeding cycle of 28 days that consisted of either 28 days feeding of diet D1 or D2 or 21 days feeding with D1 diet and 7 days with either D3 or D4 diet. Different treatments were T1 (D1 for 28 days), T2 (D2 for 28 days), T3 (D1 for 21 days and D2 for 7 days), T4 (D1 for 21 days and D3 for 7 days) or T5 (D1 for 21 days and D4 for 7 days). Fingerlings were sampled after three feeding cycles (84 days). Higher ( P  < 0.05) growth performance and protein utilization efficiency were found in the T3 group, which was similar to the T2 group. The blood count, NBT, lysozyme activity, serum parameters and stress indicator parameters also complement for the better immunity in the T2 and T3 groups. Therefore, it could be concluded that fingerlings feeding alternately a low‐protein diet (D1 ) for 21 days followed by a normal‐protein diet (D2 ) for 7 days in a cycle of 28 days for 84 days maintained better growth and health status.